1985
DOI: 10.1113/expphysiol.1985.sp002905
|View full text |Cite
|
Sign up to set email alerts
|

The ORIGINS AND CHARACTERISTICS OF CROSS‐CORRELATED ACTIVITY BETWEEN Γ‐MOTONEURONES IN THE CAT

Abstract: SUMMARYCross-correlation analysis of the naturally occurring discharges of y-motoneurones to gastrocnemius and soleus muscles has revealed a tendency towards synchronized firing in the decerebrated, spinal cat. The primary feature of the cross-correlation between two ymotoneurones is a symmetrical peak centred at time zero with reference to discharges at the level of the cell bodies in the ventral horn of the spinal cord. The peak has a half-width in the range 3-10 ms. Secondary features of the correlograms ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 26 publications
(54 reference statements)
3
58
0
Order By: Relevance
“…It is possible that if more spikes had been included in the analysis (typically, approximately 5000 spikes from each spike train were used), small central peaks would have been seen; that is, there may have been a small degree of synchrony present but we were unable to detect it. Quantitative estimation of the amount of synchrony present is complicated by the fact that it is inversely affected by the discharge frequency of the contributing units (Ellaway & Murthy, 1985). In the present study, we found that the average firing rate of the units in the thumb abductor muscles, for a contraction of 10-20% MVC, was about 16 Hz over the age range 4-11 years and then decreased with increasing age until the adult value of about 13 Hz was reached.…”
Section: Discussionmentioning
confidence: 49%
“…It is possible that if more spikes had been included in the analysis (typically, approximately 5000 spikes from each spike train were used), small central peaks would have been seen; that is, there may have been a small degree of synchrony present but we were unable to detect it. Quantitative estimation of the amount of synchrony present is complicated by the fact that it is inversely affected by the discharge frequency of the contributing units (Ellaway & Murthy, 1985). In the present study, we found that the average firing rate of the units in the thumb abductor muscles, for a contraction of 10-20% MVC, was about 16 Hz over the age range 4-11 years and then decreased with increasing age until the adult value of about 13 Hz was reached.…”
Section: Discussionmentioning
confidence: 49%
“…The width of the peak (n bins) was measured from the cusum of the cross-correlogram. The strength of short-term synchrony for each pair was estimated with the k' value (k' = xÏnm, where x is the sum of the counts in the n bins of the peak, and m is the mean count expected to fall into any bin by chance, which was calculated from fifty bins in flat parts of the histogram on each side of the peak; Ellaway & Murthy, 1985). The strength of common drive of motor unit pairs was determined for 20-50 s of the 3 min contraction in 3-5 s epochs distributed throughout the trial, using the method of De Luca et al (1982): the algorithm is given in the Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…For the computational synchronization index (SI comp ), we used a cross-correlogram identical to those used for experimental synchrony indices (Bremner et al, 1991a;Datta and Stephens, 1990;Ellaway and Murthy, 1985;Logigian et al, 1988;Nordstrom et al, 1992;Wiegner and Wierzbicka, 1987), with lag times from −100 ms to 100 ms and 1-ms bins, with lag times centered at each bin. An event is counted each time a response spike from one train is within ±100 ms of a reference spike in the other train.…”
Section: Spike Train Generationmentioning
confidence: 99%
“…Instead of expending computational resources on finding peak regions by variance methods or visually identifying peak regions for thousands of motor unit pairs using CUSUM deflections (Ellaway and Murthy, 1985, Wiegner and Wierzbicka 1987, Nordstrom et al 1992, the peak region was fixed at −4.5 ms ≤ lag time ≤ +4.5 ms (the 9 central bins). The computational SI comp index was then used to express synchrony as the ratio of the mean bin population within (binpop pk ) and outside (binpop npk ) the peak region, as shown in equation (5).…”
Section: Spike Train Generationmentioning
confidence: 99%